2018
DOI: 10.1016/j.nima.2018.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of proton-induced radioactivation background in hard X-ray telescopes: Geant4-based simulation and its demonstration by Hitomi’s measurement in a low Earth orbit

Abstract: Hard X-ray astronomical observatories in orbit suffer from a significant amount of background due to radioactivation induced by cosmic-ray protons and/or geomagnetically trapped protons. Within the framework of a full Monte Carlo simulation, we present modeling of in-orbit instrumental background which is dominated by radioactivation. To reduce the computation time required by straightforward simulations of delayed emissions from activated isotopes, we insert a semi-analytical calculation that converts product… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The background of irradiated CdTe-DSD was thoroughly investigated with Monte Carlo simulations in our previous work. 4 In that paper, we successfully reproduced the observed background of CdTe-DSD with the simulations, and revealed that it is dominated by the protoninduced radioactivation of the CdTe-DSD itself.…”
Section: Proton-induced Radioactivation Background In the Cdte-dsdmentioning
confidence: 59%
See 1 more Smart Citation
“…The background of irradiated CdTe-DSD was thoroughly investigated with Monte Carlo simulations in our previous work. 4 In that paper, we successfully reproduced the observed background of CdTe-DSD with the simulations, and revealed that it is dominated by the protoninduced radioactivation of the CdTe-DSD itself.…”
Section: Proton-induced Radioactivation Background In the Cdte-dsdmentioning
confidence: 59%
“…We used a Monte Carlo simulation framework COMPTONSOFT,11 identical to that used in a previous work on the radioactivation background of the CdTe-DSD. 4 In the COMPTONSOFT, interactions between incident particles and detector materials are simulated by the software based on the GEANT4 toolkit library. [12][13][14] In addition, detailed detector responses due to the charge carrier transport inside semiconductor detectors are also implemented.…”
Section: Monte Carlo Simulations Of the Hxi Backgroundmentioning
confidence: 99%
“…The background of irradiated CdTe-DSD was thoroughly investigated with Monte Carlo simulations in our previous work. 7 In that paper, we successfully reproduced the observed background of CdTe-DSD with the simulations, and revealed that it is dominated by the proton-induced radioactivation of the CdTe-DSD itself.…”
Section: Proton-induced Radioactivation Background In the Cdte-dsdmentioning
confidence: 60%
“…In order to test the reconstruction algorithm developed in this work, we apply it to a simulation data set generated by ComptonSoft, a software package of Geant4-based simulation and data analysis for Compton telescopes [26,27,28]. The algorithm has a great advantage in the event reconstruction of Compton telescopes with a large sensitive volume.…”
Section: Numerical Experimentsmentioning
confidence: 99%